An Untypical Case of Gouty Infiltration of Both Peroneal Tendons and a Longitudinal Lesion of the Peroneus Brevis Tendon Mimicking Synovial Sarcoma - Konstantinos Anagnostakos; Andreas Thiery; Christof Meyer; Octavian Tapos (Case Reports in Orthopedics)
We present a case of a 70-year-old male patient with an untypical gout infiltration of the peroneal tendons mimicking synovial sarcoma. The patient had a negative history of gout at initial presentation in our department. Magnetic resonance imaging of the region revealed a finding highly suspicious for synovial sarcoma of the peroneal tendons. Open biopsy was performed. Histopathological examination of the tissue samples demonstrated the presence of gout with no signs of malignancy. The gout infiltration was excised in a subsequent surgery. Orthopedic surgeons should be aware of the potential manifestation of gout in tendons and bear this in mind in the differential diagnosis of soft tissue tumors.